The Role and Place of Mini–Approach Cholecystectomy in Surgery for Chronic Calculous Cholecystitis - K., Botirov A.; B., Solijonov Z.; .Z., Otakuziev A; A., Botirov J. (RA Journal of Applied Research, 2022)
The authors note that cholelithiasis, according to epidemiological indicators, occupies one of the leading places in the structure of the incidence of the abdominal organs. At the same time, cholecystectomy (CE) from the mini–access is not considered an alternative to laparoscopic cholecystectomy (LCE) and is an independent method. It is also noted that mini–access CE has a number of advantages and preferences compared to laparoscopic access. Compared to LCE, the incidence of postoperative complications after CE from the mini–access is significantly lower and amounts to 1.9%–4.9%. The percentage of postoperative mortality is approximately the same and ranges from 0.8–1.2%, but it should be borne in mind that CE from the mini–access is most often performed in patients with complicated forms of cholelithiasis. Along with LCE, who routinely use CE from a mini–access, its use is undeservedly limited by many surgeons due to lack of experience.